The Yin and Yang of Pneumolysin During Pneumococcal Infection - Pereira, Joana M.; Xu, Shuying; Leong, John M.; Sousa, Sandra (Frontiers in Immunology, 2022)
Pneumolysin (PLY) is a pore-forming toxin produced by the human pathobiont Streptococcus pneumoniae, the major cause of pneumonia worldwide. PLY, a key pneumococcal virulence factor, can form transmembrane pores in host cells, disrupting plasma membrane integrity and deregulating cellular homeostasis. At lytic concentrations, PLY causes cell death. At sub-lytic concentrations, PLY triggers host cell survival pathways that cooperate to reseal the damaged plasma membrane and restore cell homeostasis. While PLY is generally considered a pivotal factor promoting S. pneumoniae colonization and survival, it is also a powerful trigger of the innate and adaptive host immune response against bacterial infection. The dichotomy of PLY as both a key bacterial virulence factor and a trigger for host immune modulation allows the toxin to display both “Yin” and “Yang” properties during infection, promoting disease by membrane perforation and activating inflammatory pathways, while also mitigating damage by triggering host cell repair and initiating anti-inflammatory responses. Due to its cytolytic activity and diverse immunomodulatory properties, PLY is integral to every stage of S. pneumoniae pathogenesis and may tip the balance towards either the pathogen or the host depending on the context of infection.